2020
DOI: 10.1111/psyg.12563
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of yokukansan compared with clonazepam for rapid eye movement sleep behaviour disorder: a preliminary retrospective study

Abstract: Aim: Rapid eye movement sleep behaviour disorder (RBD) is characterized by abnormal behaviours accordant with nightmares during rapid eye movement sleep and is considered a prodromal marker of dementia with Lewy body. Most common in the elderly population, RBD is generally treated with clonazepam (CZP), a long-term acting benzodiazepine antiepileptic. As such, alternative drugs for RBD are urgently needed to minimize the adverse effects peculiar to benzodiazepines. The efficacy of yokukansan (YKS), a tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Results of randomized clinical trials, most of them involving a limited number of patients, have shown the short-term efficacy of the anticholinesterase drugs rivastigmine [67,68] and 5-hydroxytryptophan [75] and the herbal medicine yokukansan [81,82], as well as the lack of efficacy of nelotanserin [74] and cannabidiol [79]. Memantine has shown some degree of medium-term efficacy in the reduction of RBD symptoms in patients with LBD and dementia associated with PD [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of randomized clinical trials, most of them involving a limited number of patients, have shown the short-term efficacy of the anticholinesterase drugs rivastigmine [67,68] and 5-hydroxytryptophan [75] and the herbal medicine yokukansan [81,82], as well as the lack of efficacy of nelotanserin [74] and cannabidiol [79]. Memantine has shown some degree of medium-term efficacy in the reduction of RBD symptoms in patients with LBD and dementia associated with PD [83].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of antidepressants and/or serotoninergic drugs on RBD are summarized in Table 6. The herbal medicine yokukansan or Yi-Gan San has led to improvements of RBD symptoms in a short case series [80] and two retrospective analyses of clinical records [81,82] (in one of them via a comparison with clonazepam [82]).…”
Section: Herbalsmentioning
confidence: 99%
“…Two retrospective observational studies demonstrated an improvement in the frequency of acting out during sleep episodes. 58,59…”
Section: Yokukansan (Yi-gan San)mentioning
confidence: 99%
“…Drugs containing Uncaria appear to ameliorate sleep in different ways. For instance, YKS was shown to improve sleep disturbances (sleep time, quality, and sleep-related limb movements) in adults suffering from REM sleep behavior disorder or dementia [ 6 , 50 , 51 , 52 ]. It was also reported to improve sleep quality in patients with insomnia [ 7 ] and children with nocturnal enuresis [ 53 ].…”
Section: Introductionmentioning
confidence: 99%